Clinical observation of moxibustion combined with cupping therapy in the treatment of constipation of deficiency of Qi and blood in convalescent patients with stroke (艾灸联合拔罐疗法改善脑卒中恢复期患者气血亏虚型便秘的临床观察) - TU Li (涂丽); YU Yanlan (余艳兰) (中西医结合护理)
Objective To investigate the effect of moxibustion combined with cupping therapy in relieving constipation of deficiency of Qi and blood in convalescent patients with stroke. Methods A total of Sixty-four patients with constipation of deficiency of Qi and blood after stroke were randomly divided into control group and observation group, with 32 patients in each group. All patients receive routine treatment and nursing, and those in the observation group were given moxibustion combined with cupping therapy. Traditional Chinese Medicine symptom score scale was used to evaluate the severity of constipation before and after treatment. The therapeutic effects in two groups were compared. Results Scores of constipation symptoms such as defecation frequency, defecation duration, fecal characteristics, difficulty in defecation and desire to defecate in the observation group were significantly lower than those in the control group after one and two courses of intervention (P＜0. 05). The total effective rate in the observation group was higher than that in the control group (90. 63% vs. 56. 25%, P＜0. 01). Conclusion Moxibustion combined with cupping therapy can effectively relieve the symptoms of constipation caused by Qi and blood deficiency in convalescent patients with stroke. (目的 观察艾灸联合拔罐疗法改善脑卒中恢复期患者气血亏虚型便秘的临床疗效。方法 采用便利抽样法选取2023年7月—2024年9月在湖南省某三级甲等中医院神经内科住院的64例气血亏虚型便秘脑卒中恢复期患者为研究对象, 按照随机数字表法分为对照组(n=32)和观察组(n=32)。两组患者均给予常规治疗和护理, 观察组增加艾灸联合拔罐疗法。对比两组患者便秘症状分级评分, 评价干预效果。结果 干预1个疗程和2个疗程后, 观察组便秘症状中排便频率、每次排便时间、粪便性状、排便难度和便意的分级评分低于对照组, 差异有统计学意义(P＜0. 05)。观察组总有效率90. 63%(29/32), 高与对照组的56. 25%(18/32), 差异有统计学意义(P＜0. 01)。结论 艾灸配合拔罐疗法可有效改善脑卒中恢复期气血亏虚型便秘患者症状, 对脑卒中康复有积极作用。)